Tomographic aspects of common variable immunodeficiency suggestive of lymphocytic granulomatous interstitial lung disease: a systematic review - Costa Amaral de Sousa, Lucas; Amorim, Caroline Alencar; Hunt, Shannon de Oliveira; Santana, Juliana Silva de; Marques, Danilo de Santana; Motta, Daniela de Lucena (Brazilian Journal of Implantology and Health Sciences, 2025)
Objective: Common variable immunodeficiency (CVID) is a primary antibody deficiency characterised by hypogammaglobulinemia, leading to the occurrence of infections and at times, the development of diffuse lesions with granulomatous characteristics and lymphoproliferative histopathological patterns. Granulomatous lymphocytic interstitial lung disease (GLILD) is a rare form of interstitial lung disease where imaging exams play a crucial role, therefore this article aims to assess the prevalence of tomographic findings and evaluate whether bronchiolitis and ground glass opacity are suggestive findings for the diagnosis of GLILD in patients with CVID without a previous GLILD diagnosis. Method: a systematic review using the prisma methodology was conducted with five descriptors across four databases, covering publications from 2012 to 2022 in the portuguese, english, and spanish languages. Results: out of 234 initial results, 26 articles were included, representing a total of 775 analysed CVID patients. Various radiographic abnormalities were identified, with notable findings including bronchiectasis, pneumonia, atelectasis, among others. Conclusion: the results indicate that it is not possible to establish a pattern of tomographic findings, demonstrating the heterogeneity in the presentation of glild.